Effect of harvest on the different fertilization methods of asparagus (Asparagus officinalis L.) - Erdős, Zsuzsa (Acta Agraria Debreceniensis, 2016)
The experiments were performed in the University of Debrecen Centre for Agricultural Research Institute of Nyíregyháza of 1500 m2 asparagus plantation in 2011. We were determind the number of shoots, plant height, fold thickness and yield of asparagus hybrid. I studied to the effects of various cropyear is addition Grolim hybrid asparagus growth and development. Compared to previous years, 2014 was unusually wet and cold weather conditions which causes the plantation has developed outstanding. The soil temperature early and dynamic increase due to, the harvest had started a one month earlier 2014 than the 2013. The experiment asparagus harvested from lower yields as a result of the extremely dry spring in 2015.